Metaverse for education – Virtual or real? - Hussain, Sajjad (Frontiers in Education, 2023)
Metaverse is considered an extension of the Internet that is expected to revolutionise our social and economic lives by offering seamless interactions in the virtual worlds. Some believe that the Metaverse is destined to fail while others envisage Metaverse as integral part of future life, same as the Internet in today’s world. While the jury is still out on whether the Metaverse would eventually be materialised to its full potential, billions have been invested into to the development of the Metaverse and its related technologies by the technology giants such as Meta, Microsoft, Apple. The Metaverse promises to bring a step change in every walk of life and Education sector is no exception. A true realisation of the Metaverse will make the geographical boundaries disappear making the education accessible to the least privileged communities. At the same time, the virtual worlds with immersive experience of usually less accessible resources would provide at-scale resource sharing throughout the world. The Metaverse would enable seamless access of Stanford labs, for instance, to someone in Africa to do collaborative experiments in the virtual worlds. This Perspective presents the status of the Metaverse in Education and the future of Education with the integration of the Metaverse. In the end it presents the author’s perspective on the practicalities and challenges of the Metaverse in Education. The author believes that despite all the hype created around Metaverse, it will take a pandemic-like disruption for the academic world to truly embrace and integrate the Metaverse in Education sector.